Design, synthesis and molecular modeling of new 4-phenylcoumarin derivatives as tubulin polymerization inhibitors targeting MCF-7 breast cancer cells. Issue 12 (23rd July 2018) - Batran, Rasha Z.; Kassem, Asmaa F.; Abbas, Eman M.H.; Elseginy, Samia A.; Mounier, Marwa M.
Graphical abstract: Highlights: A new set of 4-phenylcoumarins was designed and synthesized. Cytotoxic effects against MCF-7 were assessed. Compounds 3a, 3b and 3f were potent TUBb polymerization inhibitors. 3a induced cell cycle arrest at G2/M phase and activated caspase-7. Molecular docking and dynamics studies were performed. Abstract: A new set of 4-phenylcoumarin derivatives was designed and synthesized aiming to introduce new tubulin polymerization inhibitors as anti-breast cancer candidates. All the target compounds were evaluated for their cytotoxic effects against MCF-7 cell line, where compounds 2f, 3a, 3b, 3f, 7a and 7b, showed higher cytotoxic effect (IC50  = 4.3–21.2 μg/mL) than the reference drug doxorubicin (IC50  = 26.1 μg/mL), additionally, compounds 1 and 6b exhibited the same potency as doxorubicin (IC50  = 25.2 and 28.0 μg/mL, respectively). The thiazolidinone derivatives 3a, 3b and 3f with potent and selective anticancer effects towards MCF-7 cells (IC50  = 11.1, 16.7 and 21.2 μg/mL) were further assessed for tubulin polymerization inhibition effects which showed that the three compounds were potent tubulin polymerization suppressors with IC50 values of 9.37, 2.89 and 6.13 μM, respectively, compared to the reference drug colchicine (IC50  = 6.93 μM). The mechanistic effects on cell cycle progression and induction of apoptosis in MCF-7 cells were determined for compound 3a due to its potent and selective cytotoxic effects in addition to its promising tubulin polymerization inhibition potency. The results revealed that compound 3a induced cell cycle cessation at G2/M phase and accumulation of cells in pre-G1 phase and prevented its mitotic cycle, in addition to its activation of caspase-7 mediating apoptosis of MCF-7 cells. Molecular modeling studies for compounds 3a, 3b and 3f were carried out on tubulin crystallography, the results indicated that the compounds showed binding mode similar to the co-crystalized ligand; colchicine. Moreover, pharmacophore constructed models and docking studies revealed that thiazolidinone, acetamide and coumarin moieties are crucial for the activity. Molecular dynamics (MD) studies were carried out for the three compounds over 100 ps. MD results of compound 3a showed that it reached the stable state after 30 ps which was in agreement with the calculated potential and kinetic energy of compound 3a .